Metabolic relay gene of aphid and primary symbiont as RNAi target loci for aphid control - Li, Qian; Cheng, Yu; Fan, Jia; Chen, Julian (Frontiers in Plant Science, 2023)
Aphids form a stable and mutually beneficial relationship with their primary symbiont Buchnera aphidicola, which play an important role in providing the missing nutrients to the host aphid. Based on the genome sequence of wheat aphid Siotobion miscanthi and its primary symbiont Buchnera that we obtained in our previously study, we identified a metabolic relay gene, ilvA, involved in the isoleucine synthesis pathway between aphids and Buchnera. Quantitative PCR experiments showed that ilvA was expressed at the highest level in the 2nd instar of the aphid, while the expression of this gene was significantly higher in the aphid bacteriocytes than in other tissues. Notably, this gene is localized on the aphid sex chromosome and remains highly conserved and collinearity across different aphid genomes. RNAi experiments showed that knocking down the expression of ilvA reduced the aphid body weight and production. However, the indices of mortality decreased slightly, but were not significantly different, compared to the control. The results show that the relay genes between aphids and their symbionts in the metabolism of essential nutrients have potential roles in the growth and development of aphids, meanwhile, providing target loci and new ideas for RNAi-based aphid green control strategies.